Overexpression of microRNA‐30a inhibits hepatitis B virus X protein‐induced autophagosome formation in hepatic cells. (13th February 2015) - Kumar, Satendra; Gupta, Parul; Khanal, Sweta; Shahi, Aashirwad; Kumar, Pushpendra; Sarin, Shiv K.; Venugopal, Senthil K.
Abstract : Hepatitis B virus (HBV) enters the host and survives by using several mechanisms. One of the ways that HBV survives and replicates in the host cells is by inducing autophagy. Previous reports have shown that microRNA (miRNA)‐30a inhibits autophagosome formation in cancer cells. Hence, we hypothesized that overexpression of miRNA‐30a could inhibit HBV‐induced autophagosome formation in hepatic cells. To study this, both HepG2 cells and HepG2.2.1.5 cells (HBV‐expressing stable cell line) were transfected with miRNA‐30a, and the cells were collected either for RNA isolation or protein isolation after 72 h of transfection. Beclin‐1 expression was significantly higher in untransfected HepG2.2.1.5 cells than in HepG2 cells. Western blots showed that miRNA‐30a overexpression resulted in a significant decrease in beclin‐1 expression (eight‐fold and four‐fold in HepG2 and HepG2.2.1.5 cells, respectively) and c‐myc expression, whereas the numbers of terminal deoxynucleotidyl transferase‐mediated dUTP nick end labeling (TUNEL)‐positive cells were increased. In contrast, overexpression of HBV X protein (HBx) in HepG2 cells resulted in the enhancement of beclin‐1 (six‐fold increase as compared with the empty vector‐transfected cells) and c‐myc expression, whereas the numbers of TUNEL‐positive cells were reduced. To confirm these findings, HBx and miRNA‐30a were coexpressed in HepG2 cells, and the results showed significant inhibition of autophagosome formation and beclin‐1 and c‐myc expression, whereas apoptosis increased. These data demonstrate that HBx induces autophagosome formation via beclin‐1 expression, whereas miRNA‐30a overexpression could successfully inhibit the beclin‐1 expression induced by HBx, thereby modulating autophagosome formation in hepatic cells. Abstract : Hepatitis B Virus (HBV) utilizes several mechanisms for its replication and survival in the host; autophagy being one of the key pathways in this process. Here, we showed that hepatitis B virus X protein (HBx) induces autophagosome formation by inducing beclin‐1 expression while over‐expression of miRNA‐30a inhibited beclin‐1 expression, thereby inhibiting HBx‐induced autophagosome formation in hepatic cells.